Abusive practices in competition law - Di Porto, Fabiana, 1973-; Podszun, Rupprecht, 1976-; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2018)
Abusive Practices in Competition Law tackles the difficult questions presented to competition lawyers and economists regarding abusive practices: where and when is the red line crossed in competitive advances? When is a company explicitly dominant? How do you handle those who hold superior bargaining power over others but are not classed as dominant? Including analysis of the EU as well as individual nations such as the USA, Germany, France, Italy, China, Japan, Australia and developing countries, this book presents the state of the art in abusive practices in competition law research. Drawing on a variety of experiences from different jurisdictions, the authors answer the most fundamental questions concerning abusive practices, with a special focus placed on superior bargaining power, economic dependence and unconscionable conduct as thresholds for competition law interventions. Key areas such as market definition in platform markets, use of presumption in antitrust law, commitment procedures and aggregate concentration concerns are all discussed within this context. Essential reading for competition lawyers and economists, Abusive Practices in Competition Law gives comprehensive advice and insight for those dealing with antitrust concepts and practical cases of abusive conduct.
List of contributors -- Introduction / Rupprecht Podszun and Fabiana Di Porto -- Part I: Fundamental questions of dominance and abuse -- 1. The ordoliberal concept of "abuse" of a dominant position and its impact on Article 102 TFEU / Peter Behrens -- 2. The European Commission's enforcement of abuse cases. A statistical analysis / Lorenz Marx -- 3. Presumptions and short-cut rules in abuse regulation: (where) do EU and U.S. antitrust approaches meet? / Pieter Van Cleynenbreugel -- 4. The pitfalls of market definition: towards an open and evolutionary concept / Rupprecht Podszun -- 5. Exploitative prices in European competition law / Antonio Robles Martín-Laborda -- 6. All's well that ends well? Abuse regulation in the wake of the financial crisis. The interplay between regulation and the application of competition law to the financial sector / Luís Silva Morais and Lúcio Tomé Feteira ---7. The application of Article 102 TFEU in the EU energy sector: a critical evaluation of commitments / Maria Ioannidou -- Part II: Superior bargaining power, economic dependence and abuse -- 8. Abuse without dominance in competition law: abuse of economic dependence and its interface with abuse of dominance / Mor Bakhoum -- 9. Superior Bargaining power: dealing with aggregate concentration concerns / Thomas K. Cheng and Michal S. Gal -- 10. Unilateral conduct by non-dominant firms: a comparative reappraisal / Florian Wagner-von Papp -- 11. Restraining bargaining power through competition law: superior bargaining position regulation in Japan as compared with the EU / Toshiaki Takigawa -- 12. Ex-ante and ex-post control of buyer power / Stefan Thomas -- Part III: National experiences with the regulation of abusive conduct -- 13. The application of the Chinese Antimonopoly Law to state-owned enterprises / Fang Xiaomin ---14. Unconscionable conduct in the context of competition law with special reference to retailer/supplier relationships within Australia / Allan Fels and Matthew Lees -- 15. The Italian regulation against the abuse of economic dependence at the crossroads / Valeria Falce -- 16. Unconscionable conduct in France / David Bosco -- 17. Comparative analysis of the Japanese Subcontract Act and the regulations on unfair trade practices in the EU: focus on the grocery industry / Kazuhiko Fuchikawa -- 18. An alternative perspective for assessing abuse of dominance in emerging markets / Abayomi Al-Ameen -- 19. Abuses of dominant and non-dominant position. A tale of (ir)reconcilable views? / Fabiana Di Porto -- Index.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: právo hospodářské soutěže; hospodářská soutěž; competition law; competition; e-knihy online; e-books online